Effect of phenotype and cassava planting density on phytophagous mites on the Atlantic coast - HERRERA-F., CARLOS JULIO; BRAUN, ANN (Revista Colombiana de Entomología, 1995)
Phenotypic factors such as plant morphology, and physical factors such as planting density, effects in the creation of a microclimate that influences the population growth of phytophagous mites and of their natural enemies in cassaya. Three planting densities (5,000, 10,000, and 15,000 plants per hectare) and three cassaya clones: CM 681-2 (low vigor and small leaves), M Col 1505 (vigorous and with intermediate leaves size) and M MAL-2 (very vigorous and with large leaves) were evaluated. M MAL-2 is considered to be mite susceptible, while CM 681-2 and M Col 1505 are moderately resistant. Periodic mite population evaluations were made and the leaf area was measured at three plant levels to calculate the number of mites per unit area for each genotype. At the lowest planting density (5,000 plants/ ha) the highest increase in phytophagous mites and the lowest increase in predator mites of the Phytoseiidae family were observed. The most favorable density for an increase in phytophagous mite populations was 15,000 plants/ ha. The highest number of phytoseiid mite predators was observed on the done CM 6812, where the highest density of the phytophagous mite population was also recorded.